Actividades sobre gráficos estadísticos propuestas en libros de texto de Educación Primaria - Osorio, Miluska (2022)
This paper describes the results of the activities on statistical graphics in a complete series of mathematics textbooks for primary education in Peru. The research follows a qualitative methodology, at a descriptive level, and as a method of data collection we have used content analysis. The sample corresponds to six primary school textbooks, one per level, which belong to those delivered by the Ministry of Education to public schools, chosen for their wide diffusion in the Peruvian territory. The results show disparity among the various activities, with a predominance of calculating and explaining.